Plant communities of the Thero-Salicornietea and Salicornietea fruticosae classes along the Russian coast of the Sea of Azov (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Halophytic plant communities of the Russia coast of the Sea of Azov are described using the Braun-Blanquet approach for the first time. Three variants of the ass. Salicornietum prostratae, new subass. Salicornio perennantis-Suaedetum salsae halimionetosum (class Thero-Salicornietea) and ass. Salicornio prostratae-Halocnemetum strobilaceae (class Salicornietea fruticosae) are established. The name of ass. Salicornio-Halocnemetum Korzhenevsky et Kljukin in Korzhenevsky 2000 is corrected in accordance with the rules of the International Code of Phytosociological Nomenclature.
Keywords: halophytic plant communities, syntaxonomy, coast of the Sea of Azov, maritime salt-marshes.